PERAN DIRECTOR OF PHOTOGRAPHY DALAM FILM DOKUMENTER "Jerat Dilema: Konflik Perempuan Berperan Ganda" - Amelia Sukmaputri (2021)
The documentary film 'Jerat Dilema: Conflict of Dual Roles Women' aims to visualize phenomena that occur in an expositional style and build public awareness to support women with multiple roles through the online campaign #WeSupportWomen. The author as the Director of Photography carries out the pre-production to post-production stages following the competency Standar Kompetensi Kerja Nasional (SKKNI). Several shooting techniques were used to record the interviews and show the daily life and conflicts experienced by the interviewees. This documentary film managed to reach the specified target audience and was quite influential in the public's understanding of the dual roles of women.